The Development of a Cured, Fermented Sheepmeat Sausage Designed to Minimise Species and Pastoral-Diet Flavours - Lu, Yanjun (Auckland University of Technology, 2010)
The purpose was product development to increase sheepmeat liking for consumers unhabituated to its characteristic flavour. The development has centered on a cured, fermented sausage, traditionally flavoured with garlic and rosemary, aiming to suppress the intrinsic species flavour (from branched chain fatty acids) and flavours (mainly skatole) from New Zealand’s pastoral diets. However, appearance and texture are also important for liking. Therefore, the colour and textural properties of cured, fermented sheepmeat sausage were compared with those of beef and pork equivalents. The problem of between-animal variation was overcome by comparing replicates made from meats bought on seven dates from different butchers. During fermentation over four days, samples were tested for growth of lactic acid bacteria, pH decrease, and colour and texture changes. There were no significant differences between the species. Subsequently, the flavour of fermented beef sausage was assessed by consumers where the fat was pre-treated (or not as controls) with the ovine-characterising branched chain fatty acids (BCFAs), 4-methyloctanoic acid and 4-methylnonanoic acid, as well as with the pastoral flavour- characterising compound, skatole. Beef has no BCFAs and low concentrations of skatole, and was thus ‘turned into sheepmeat’ by addition of BCFAs and skatole. The sausage mixture was in eight treatments that were combinations of cured vs. non-cured, flavoured vs. non-flavoured, added BCFAs/skatole vs. non-added. For sensory evaluation, 60 consumers tasted samples in a randomized design and completed a 9-point liking-score scale for each. Neither curing nor flavouring affected the liking of sausage treatments with or without added BCFAs/skatole. However, combined curing and flavouring significantly enhanced the liking of the added BCFAs/skatole treatment. Thus, appearance and texture of fermented sheepmeat were the same as for other species; species and pastoral flavours in sheepmeat may be more acceptable to unhabituated consumers where fermented sausage is flavoured with at least traditional European flavours.
Keywords: Sheepmeat; Cured and fermented sausage; Physicochemical properties; BCFAs and skatole; Sensory evaluation